PERLINDUNGAN TERHADAP PERS DI NEGARA YANG SEDANG BERKONFLIK MENURUT HUKUM INTERNASIONAL - Jean Bernard Myson; Abdul Rahman; Jelly Leviza (Journal of USU International Law, 2014)
ABSTRACT Release victims who were killed or wounded in armed conflict more annually increasing . International humanitarian law set in the Art . 79 Prot . Annex I to the second as the protection of civilians in armed conflict . They can not be targeted directly and can not be used as a shield . Military forces must take all necessary measures to protect civilians in conflict areas against the effects of military operations . However , Press who participated in military activities as well as any loss of immune status as civilians dlindungi by international humanitarian law . For example , by equipping themselves with the tools of armed or become a spy for the adverse party . Prisoners must not be tortured or executed without trial before an independent court . Media tools are not military facilities , even if they are used for propaganda or to incite the population to commit atrocities against racial or religious groups or other minorities . According to Art . 52 Prot . Annex I , they should be viewed as a civilian object . For example , a radio station can not be targeted directly , and must be protected against any effects of military operations . Many of the attacks against the press was never investigated because the error is managed by the recognition . The press will always be targeted but the whole international community should do its best to prevent such action . Attacks on Press are a threat to the peace and prosperity of all countries in the world . Keywords : Protection, Press, Press Release Protection, Conflict Countries